THE WOMAN IN THE BOOK OF KINGS (LITERARY STUDIES AND HERMENEUTICS) - Marudut Bernadtua Simanjuntak; Sutrisno; Marthin Steven Lumingkewas (UICELL, 2021)
In many cultures, literature, and kingdoms, the position of women, whether they are daughters, sisters, wives or mothers, often has an important position of influence and share. The existence of female characters in Biblical studies always has an important position and has a large enough influence so that it can strengthen or weaken men. In the Book of Kings, women can be found in their positions as queens, mothers, wives, and daughters who are directly involved with the King and his kingdom. This study aims to examine the position and role of women in their existence in the biblical narrative, especially the Book of Kings, where women often have very important positions and functions in a historical influence and the continuity of the kingdom. This study was carried out in the Bible, especially the Book of Kings which was studied as literature, and the researcher used a hermeneutic approach to describe the relationship between culture and customs at that time. Keywords: biblical studies, woman literature, hermeneutics, book of kings